(untitled) - Neamen, Donald A. (New York, 2012)
With its strong pedagogy, superior readability, and thorough examination of the physics of semiconductor material, Semiconductor Physics and Devices, 4/e provides a basis for understanding the characteristics, operation, and limitations of semiconductor devices.
TN398
Keywords: Chất bán dẫn,Semiconductors